Effects of Extraction and Purification Methods on Degradation Kinetics and Stability of Lycopene from Watermelon under Storage Conditions. Issue 11 (28th September 2016) - Saeid, Abu; Eun, Jong Bang; Sagor, Md. Shafiul Azam; Rahman, Atikur; Akter, Mst. Sorifa; Ahmed, Maruf
Abstract: Lycopene was extraction, isolation and purification using recrystallization, column chromatography, and preparative thin layer chromatography (TLC) methods as well as degradation kinetics of lycopene were studied at refrigerated temperature and room temperature for 3 wk from watermelon. Higher lycopene degradation was observed at refrigerated temperature as compared to ambient temperature throughout the storage periods. The highest amount of lycopene retained in recrystallization (101.69 μg/g) followed by column chromatography (18.20 μg/g) and preparative TLC (15.57 μg/g). Color parameters, half‐life time ( t 1/2 ), and color retention (% R ) were dependent on extraction, isolation, and purification methods and storage life. Recrystallization and preparative TLC were followed by first order reaction model. Preparative TLC exhibited higher activation energy than did the recrystallization and column chromatography. Therefore, the result shows that recrystallization method could apply to extract and purify lycopene from watermelon that would also be used as a natural colorant as well as value‐added product.